The Results of Kazakhstan`s Chairmanship at the Organization of Islamic Cooperation - Kokeyeva, D. M.; Momynkulov, Zh. B. (Journal of Oriental Studies, 2016)
In this article the main results of Kazakhstan`s Chairmanship at the Organization of Islamic Cooperation are analyzed in brief. The chairmanship of at the OIC is very important event in the history of Kazakhstani diplomacy. This chairmanship, undoubtedly, meets long-term national interests of Kazakhstan. Kazakhstan`s chairmanship at the OIC insures strategic opportunity and enforces its position in the region.